1978
DOI: 10.1007/bf02121228
|View full text |Cite
|
Sign up to set email alerts
|

Behavior alterations in tree shrews (Tupaia glis, Diard 1820) induced by Borna disease virus

Abstract: Intracerebral injection of Borna disease virus in tree shrews led to a persistent infection that sometimes resulted in clinical symptoms and/or specific alterations in the animals' behavior. Whereas infective virus in the brain and in the serum antibodies were always present after infection, only some of the animals showed signs of clinical disease and behavior changes. Animals kept in pairs showed especially obvious behavior alterations expressed as an exaggeration of all the components of normal social behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 9 publications
0
65
0
1
Order By: Relevance
“…As BDV infects a wide variety of animal species with a predilection for the limbic system, and occasionally induces persistent emotional, cognitive and behavioural alterations in experimental animals, including primates and their ancestors tree shrews (Tupaia glis) (Sprankel et al, 1978;Stitz et al, 1980), the question has arisen of whether the virus could also be a human pathogen and cause neuropsychiatric disorders. The first evidence of human infections was, indeed, reported in 1985: 0.43-12.5 % of patients with diverse psychiatric disorders had BDV antibodies in serum, whereas the seroprevalence in the control group was ,0.5 % (Rott et al, 1985).…”
Section: 'Human Bd'?mentioning
confidence: 99%
“…As BDV infects a wide variety of animal species with a predilection for the limbic system, and occasionally induces persistent emotional, cognitive and behavioural alterations in experimental animals, including primates and their ancestors tree shrews (Tupaia glis) (Sprankel et al, 1978;Stitz et al, 1980), the question has arisen of whether the virus could also be a human pathogen and cause neuropsychiatric disorders. The first evidence of human infections was, indeed, reported in 1985: 0.43-12.5 % of patients with diverse psychiatric disorders had BDV antibodies in serum, whereas the seroprevalence in the control group was ,0.5 % (Rott et al, 1985).…”
Section: 'Human Bd'?mentioning
confidence: 99%
“…E-mail: cchenȰmail.tcu.edu.tw Received 8 December 1998; revised and accepted 26 April 1999 of BDV infection in the pathogenesis of human mental disorders. [2][3][4][5] Evidence for the possible link between BDV infection and human mental disorders first came from seroepidemiological studies. 6,7 Several research groups have demonstrated a significantly higher seroprevalence rate of anti-BDV antibodies in psychiatric patients than in normal controls.…”
Section: Introductionmentioning
confidence: 99%
“…In animal hosts, BDV infection has a breadth of behavioral manifestations, ranging from asymptomatic to subtle changes in social affiliative behavior to fatal meningoencephalitis (Sprankel et al, 1978;Dittrich et al, 1989;Bautista et al, 1995Bautista et al, , 1994. Animal data suggest that BDV is an interesting candidate for an infectious agent in schizophrenia.…”
mentioning
confidence: 99%
“…Animal data suggest that BDV is an interesting candidate for an infectious agent in schizophrenia. Infections with BDV can result in behavioral abnormalities in the absence of an inflammatory response (Sprankel et al, 1978;Dittrich et al, 1989;Bautista et al, 1994Bautista et al, , 1995. The limbic system, a site for schizophrenia-associated pathology, is a major target for BDV replication (Narayan et al, 1983;Gosztonyi and Ludwig, 1984;Solbrig et al, 1994) and BDV infection results in early localization to hippocampus and subsequent damage to the dentate gyrus (Carbone et al, 1991).…”
mentioning
confidence: 99%